ABOUT THE PRESS ORGANIZATION “TARJIMONI AFKOR” OF MIGRANT UZBEKS - Usarov Khusniddin Dusmamatovich (New modern researchers: modern proposals and solutions, 2025)
Uzbek​ immigrants relatively many numerical become located from the regions one Pakistan Islam Karachi and the Republic of Peshawar cities was. In the 1940s and 1950s, this 3.5-4 thousand in cities person Uzbeks (Turkistanis ) live there that he did with related information occurs , archive Historical sources to the information see​ From Afghanistan Turkey Republic and India , Saudi Arabia Arabia such as to countries move discretion did compatriots first​ to Karachi arrived come , then themselves wanted to the state leaving They left .